Biological activities and safety data of kojic acid and its derivatives: A review. Issue 10 (23rd August 2022) - Zilles, Júlia Capp; dos Santos, Francielli Lima; Kulkamp‐Guerreiro, Irene Clemes; Contri, Renata Vidor
Abstract: Kojic acid presents a variety of applications for human use, especially as a depigmenting agent. Its derivatives are also proposed in order to prevent chemical degradation, prevent adverse effects and improve efficacy. The aim of this study was to peer review the current scientific literature concerning the biological activities and safety data of kojic acid or its derivatives, aiming at human use and trying to elucidate the action mechanisms. Three different databases were assessed, and the word "kojic" was crossed with "toxicity, " "adverse effect, " "efficacy, " "effect, " "activity" and "safety." Articles were selected according to pre‐defined criteria. Besides the depigmenting activity, kojic acid and derivatives can act as antioxidant, antimicrobial, anti‐inflammatory, radioprotector, anticonvulsant and obesity management agents, and present potential as antitumor substances. Depigmenting activity is due to the molecules, after penetrating the cell, binding to tyrosinase active site, regulating melanogenesis factors, leucocytes modulation and free radical scavenging activity. Hence, polarity, size and ligands are also important factors for activity. Kojic acid and derivatives present cytotoxicity to some cancerous cell lines, including melanoma, hepatocellular carcinoma, ovarian cancer, breast cancer and colon cancer. Regarding safety, kojic acid or its derivatives are safe molecules for human use in the concentrations tested. Kojic acid and its derivatives have great potential for cosmetic, pharmaceutical and medical applications.